PENGARUH KEMANDIRIAN KEUANGAN DAERAH TERHADAP KEMISKINAN DI KABUPATEN/KOTA PROVINSI ACEH - Afni Riskiyani; Muhammad Nasir (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2021)
AbstractThis research is motivated by the poverty level which is still high, and requires its own local financial resources to independently solve development problems in Aceh, including the problem of poverty. The purpose of this study is to determine the effect of regional financial independence on poverty in the District/City of Aceh Province. The method used is the panel data regression method with the best model Random Effect Model (REM). In this study, the type of data used is secondary data from 23 districts/cities in Aceh Province for the 2012-2019 period. With regional financial independence as the independent variable and poverty as the dependent variable. Data were obtained from BPS Aceh, BPS RI, and BPKA and BPK RI. The results of this study indicate that regional financial independence has a significant and negative effect on poverty, while economic growth has no significant effect on poverty.Keywords: Regional Financial Independence, Economic Growth, Poverty